New Latrunculiidae genus (Porifera, Poecilosclerida) from the Madagascar Ridge - Payne, Robyn; Samaai, Toufiek; Kelly, Michelle (Zootaxa, 2022)
Family Latrunculiidae Topsent, 1922 comprises seven genera: Latrunculia Barboza du Bocage, 1869; Sceptrella Schmidt, 1870; Strongylodesma Lévi, 1969; Tsitsikamma Samaai & Kelly, 2002; Cyclacanthia Samaai & Kelly in Samaai et al. (2004); Bomba and Latrunclava Kelly, Reiswig & Samaai in Kelly et al. (2016) (Samaai & Kelly 2002; Kelly et al. 2016; Samaai et al. 2020), with 83 valid species predominantly in the Southern Hemisphere (de Voogd et al. 2021). Latrunculiidae are differentiated primarily on the form and ornamentation of the diagnostic discorhabd microscleres (see Fig. 1) which may be anisodiscorhabds (Latrunculia, Bomba), isospinodiscorhabds (Cyclacanthia), and isochiadiscorhabds (Tsitsikamma). These may be accompanied by an additional longer microsclere, the amphiclad sceptre and anisoconicorhabd, in Sceptrella and Latrunclava, respectively. Here we describe a new latrunculid genus and species, Biverticillus tenuissimus gen. et sp. nov., from Walters Shoal on the Madagascar Ridge south of Madagascar in the Western Indian Ocean (Fig. 1A), the diagnostic microscleres of which are anisospinodiscorhabds, with two centrally located equidiametral whorls, equally spaced between each other and the apical whorl and manubrium. The microscleres are aniso- in their form because the apical and basal substructures differ slightly in the angle of repose of the spines.